The General Theory of Magnitudes
As a continuing of the previous Theory of Magnitudes, this a General Theory The previous theory dealt only with the closest star in a ratio of its greatest inverse apparent magnitude. My new theory shows the distance between 2 stars anywhere on a photograph of the nights sky using centimeters. I am extending that beginning formula adding on a new equation with the integral calculus formula using the number value at that given to be raised to exponent 2 divided by 2 . All stars are using inverse Apparent Magnitudes like my first paper. My new formulas as stated 1+ Inverse Apparent Magnitudes one = Q 1 1 + Inverse Apparent Magnitude two = Q2 (Q1 + Q2) – (Q1 – Q2) times 2.5 divided by / (Q1 + Q2) + (Q1- Q2) times 8 pi take the square root of that by which was divided. take the natural logarithm of that and you get the value P take P squared and then divide P by 2 . call all of this formula W My second equation ; Euler’s number raised to its exponent is such ; total addition of the inverse apparent magnitudes in a centimeter using times that in centimeter plus one times 8 pi . . take natural logarithm of that total using square root of total of this divided by 3 pi Take this second equation and square it the multiply this equation called Y by w then subtract this total by w ;Then divide the previous equation by the Natural Logarithm in This set of the Inverse apparent magnitude of the reference star raised to the exponent of 10